2006
DOI: 10.1124/jpet.105.099929
|View full text |Cite
|
Sign up to set email alerts
|

The Human Organic Cation Transporter-1 Gene Is Transactivated by Hepatocyte Nuclear Factor-4α

Abstract: The organic cation transporter-1 (OCT1) mediates the hepatocellular uptake of cationic drugs and endobiotics from sinusoidal blood. The uptake rates of these compounds may depend on OCT1 expression level. Because little is known about the regulation of the human OCT1 (hOCT1) gene, we characterized the hOCT1 promoter with respect to DNA-response elements and their binding factors. By computer analysis, we identified two adjacent putative DNA-response elements for the liverenriched homodimeric nuclear receptor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 39 publications
1
83
0
3
Order By: Relevance
“…HNF1␣ transcriptional activator did not strikingly correlate with fibrosis staging (K. Nakai, unpublished data). Expression of human OCT1 was activated by HNF4␣, according to a study that used a luciferase reporter assay (Saborowski et al, 2006). Expression of HNF4␣ was also not correlated with fibrosis staging (K. Nakai, unpublished data), which suggests that HNF4␣ by itself does not fully explain the mechanisms involved in the decrease in OCT1 expression in chronic hepatitis C patients.…”
Section: Discussionmentioning
confidence: 99%
“…HNF1␣ transcriptional activator did not strikingly correlate with fibrosis staging (K. Nakai, unpublished data). Expression of human OCT1 was activated by HNF4␣, according to a study that used a luciferase reporter assay (Saborowski et al, 2006). Expression of HNF4␣ was also not correlated with fibrosis staging (K. Nakai, unpublished data), which suggests that HNF4␣ by itself does not fully explain the mechanisms involved in the decrease in OCT1 expression in chronic hepatitis C patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 13 of 29 hOCT SNPs were detected in the 5Ј-UTRs of the individual transporter genes, and several SNPs showed relatively high frequency (Ͼ 30%), which raises the possibility that the SNPs in the 5Ј-UTRs may affect the regulation of expression of these transporters. The hOCT1 gene has been reported to be transactivated by hepatocyte nuclear factor-4␣ (HNF-4␣), and the mRNA expression of organic cation transporters in liver, kidney, and duodenum is altered differently after targeted disruption of the transcription factor HNF-1␣ (Maher et al, 2006;Saborowski et al, 2006). Site-directed mutagenesis of HNF-4␣ binding site in the promoter region of the hOCT1 gene more strongly decreased luciferase activity of reporter construct hOCT1(Ϫ2620/ϩ116)mut than that of wild-type reporter construct (Saborowski et al, 2006).…”
Section: Polymorphisms Of Hocts In Korean Subjectsmentioning
confidence: 99%
“…The hOCT1 gene has been reported to be transactivated by hepatocyte nuclear factor-4␣ (HNF-4␣), and the mRNA expression of organic cation transporters in liver, kidney, and duodenum is altered differently after targeted disruption of the transcription factor HNF-1␣ (Maher et al, 2006;Saborowski et al, 2006). Site-directed mutagenesis of HNF-4␣ binding site in the promoter region of the hOCT1 gene more strongly decreased luciferase activity of reporter construct hOCT1(Ϫ2620/ϩ116)mut than that of wild-type reporter construct (Saborowski et al, 2006). Moreover, Shu et al (2001) reported steroid hormone-mediated regulation of OCT2 in MDCK cells.…”
Section: Polymorphisms Of Hocts In Korean Subjectsmentioning
confidence: 99%
“…Известно, что регуляция экс-прессии ОСТ осуществляется как на уровне транскрипции, так и на уровне белка. Так, в промоторной части гена ОСТ1 обнаружены два участка для связи с ядерным фактором гепатоцитов (HNF-4α), который активирует экспрессию транспортера [4]. Предполага-ют, что в промоторной части гена ОСТ2 на-ходятся участки, чувствительные к стеро-идным гормонам, так как показано, что при их действии повышается уровень экспрессии и активности ОСТ2 в клеточной культуре MDCK [5].…”
Section: экспрессия транспортеров органических катионов и ее регуляцияunclassified